Digital Platform for Soil Health Monitoring and Management: Data Model Documentation - Burry, Sukanya; Rozario, Gilbert; Patil, Mukund (International Crops Research Institute for the Semi-Arid Tropics, 2024)
This Data Model Documentation is a comprehensive guide describing the structure, relationships, and specifications of a database system used to develop the digital soil health monitoring platform. It serves as a blueprint for database design and implementation, ensuring that all stakeholders—including business analysts, database developers, and system administrators—have a shared understanding of how data is organized and managed.